Generative Pre-trained Transformer 3: features and capabilities - Buzovsky, K. S. (My University, 2021)
We can conclude that Generative Pre-trained Transformer 3 is a unique and impressive technology, but it also has serious drawbacks. This will not allow him to fully replace a person in the future.
Keywords: Transformer; neural network; language model; machine learning